The deletion of the arginine vasopressin 1a receptor impairs sexual and maternal behavior - Aspesi, D.; Sambor, E.; Stoehr, M. C.; Taylor, J.; Grieb, Z. A.; Huhman, K. L.; Albers, H. E. (Frontiers in Endocrinology, 2025)
IntroductionArginine-vasopressin (AVP) and its V1a receptor (V1aR) within the social behavior neural network are critical modulators of social behavior across species. Using CRISPR-Cas9-mediated gene editing, we previously demonstrated that Syrian hamsters of both sexes with V1aR knockout (V1aRKO) exhibit elevated social communication (i.e., odor-induced flank marking) and aggression compared to wild-type (WT) littermates. While most AVP research has focused on males, V1aRs have also been implicated in female sexual and maternal behaviors. Here, we investigated the effects of V1aRKO on reproductive and maternal behavior in adult female hamsters. MethodsTo assess mating behavior, a sexually experienced male hamster was introduced into the home cage of a virgin, estrus female, and their interactions were video-recorded for 30 minutes following the male's first ejaculation or until the female displayed aggression. To evaluate maternal care, home-cage behavior was video-recorded for 5 minutes on postpartum days (PPD) 0 to 3, across four timepoints per day (two times in the dark and two in the light phase), and pup-directed and non-directed behaviors were quantified.ResultsV1aRKO and heterozygous (Het) females received significantly fewer and shorter-duration mounts from males than did WT females, suggesting reduced sexual receptivity or attractiveness. Other copulatory and social behaviors, including aggression, during the observation period were unaffected. In regard to maternal behavior, V1aRKO females exhibited reduced pup-directed behaviors relative to Het and WT dams, although time spent in the nest was comparable across groups. V1aRKO females also engaged in more non-maternal behaviors (e.g., self-grooming, digging, and burying) than did Het or WT dams.ConclusionsThese findings support the hypothesis that V1aRs are essential for the robust expression of female sexual receptivity and maternal caregiving in Syrian hamsters. This work underscores the importance of studying the AVP system across sexes and species to fully understand its role in regulating complex social behaviors.